Assessment of sport orientation in the field of water sports - Thanopoulos, V.; Nikolopoulos, G.; Kaloupsis, S.; Heropoulou, H.; Diafas, V.; Platanou, T. (Biomechanics and Medicine in Swimming IX, 2003)
INTRODUCTION Several studies refer to the athletics orientation with the aim to examine the individual differences relating to sports attitude as well as to motives that lead into participation. However, similar studies of athletic orientation in the field of aquatic sports are missing. The aim of this research is to examine the differences in factors that influence athletics orientation in the field of aquatic sports with regard to a) both men and women and b) sports for men and women separately. METHODS 1272 athletes of individual and collective games participated in the research relating to swimming, water polo, diving, synchronised swimming, rowing, kayak, and technical swimming) from all over Greece (656 men and 616 women). They filled in the Greek version of Sports Orientation Questionnaire (SOQ - Gill & Deeter 1998, Karteroliotis, 1995). It comprises of three (3) parameters, namely fighting spirit, victory and aim. They are assessed in a five-grade scale. RESULTS The analysis of variance showed significant statistical differences with regard to athletics orientation with men to perform better vis a vis women in the whole sample (p.<.001). In addition, there are significant differences between men and women concerning the fighting spirit and victory (p.<.001). DISCUSSION The results of the research showed significant statistical difference for the three abovementioned parameters between men and women. Men perform better in the field of fighting spirit of the athletics orientation. This implies than men are more fight-spirit oriented than women who appear to be more sensible and quiet. Furthermore, there is a significant statistical difference among sport games (individual and collective ones) for men and women with respect to the fighting spirit and victory notion. The impact of the various parameters on the athletics orientation results in useful conclusions concerning the personality characteristics of each athlete.